2014
DOI: 10.12659/pjr.889983
|View full text |Cite
|
Sign up to set email alerts
|

Rounded atelectasis of the lung: A pictorial review

Abstract: SummaryRounded atelectasis of the lung is well described in medical literature, but still difficult to diagnose. Since lesions give no clinical symptoms in patients, radiologists are often the first to recognize the round lesion in an X-ray picture or a CT scan. Rounded atelectasis is an atypical form of lung collapse that usually occurs adjacent to scarred pleura and can be mistaken for lung cancer. Patients with rounded atelectasis have a history of asbestos exposure or pleural effusion due to various causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 10 publications
0
42
1
Order By: Relevance
“…Rounded atelectasis is more common in men (80%) than in women. The most common cause of rounded atelectasis (RA) is occupational exposure to asbestos [ 29 , 30 ]. The direct mechanism for the development of rounded atelectasis has not been fully explained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rounded atelectasis is more common in men (80%) than in women. The most common cause of rounded atelectasis (RA) is occupational exposure to asbestos [ 29 , 30 ]. The direct mechanism for the development of rounded atelectasis has not been fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…The direct mechanism for the development of rounded atelectasis has not been fully explained. According to one of the theories [ 29 ], pleural fluid causes local atelectasis due to the pressure on the adjacent lung. If the rate of fluid pleural accumulation exceeds the absorptive capacity of adjacent alveoli, visceral pleura damage occurs with formation of a fissure and translocation of the lung towards that fissure.…”
Section: Discussionmentioning
confidence: 99%
“…Atelectasis is the collapse or closure of a lung, resulting in reduced or absent gas exchange, which is caused by various lung diseases such as inflammatory nodules, tuberculosis, asthma, chronic obstructive pulmonary disease, and bronchiectasis, resulting in mechanical alveolar obstruction . Clinically significant atelectasis is generally identified by preoperative chest radiography or CT scan . Therefore, based on the results of a preoperative CT scan, surgeons can accurately identify the tumor, benign lung lesion, or atelectasis in the operative field.…”
Section: Discussionmentioning
confidence: 99%
“…44 Clinically significant atelectasis is generally identified by preoperative chest radiography or CT scan. 45 Therefore, based on the results of a preoperative CT scan, surgeons can accurately identify the tumor, benign lung lesion, or atelectasis in the operative field. In addition, chest physiotherapy bronchodilators, fiberoptic bronchoscopy, positive end-expiratory pressure, and surfactants have been described by many researchers as treatment modalities for atelectasis and shown to be effective in the resolution of atelectasis.…”
Section: Limitationsmentioning
confidence: 99%
“…Rounded atelectasis (also called atelectatic pseudotumor, folded lung, or Blesovsky syndrome) is a condition extensively reported in human medicine, which describes focal, peripheral lung collapse caused by pleural adhesions and fibrosis secondary to chronic pleural effusions and pleuritis. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This condition was first published in the 1960s by Blesovsky who reported that peripheral pulmonary nodules sampled during thoracotomies in humans frequently resembled benign folded lung, which initiated research endeavors for defining the imaging characteristics, etiologies, and pathophysiology of this condition. [1][2][3] Asbestos inhalation is the most documented factor associated with this condition in humans, although all types of pleural effusion can potentially induce it.…”
Section: Introductionmentioning
confidence: 99%